As dawn breaks [large type] - Breslin, Kate (Thorndike Press large print Christian romance series., 2022)
"Her daring bid for freedom could be her greatest undoing. Amid the Great War in 1918 England, munitions worker Rosalind Graham is desperate to escape the arranged marriage being forced on her by her ruthless guardian and instead follow her own course. When the Chilwell factory explodes, killing hundreds of unidentified workers, Rose realizes the world believes she perished in the disaster. Seizing the chance to escape, she risks all and assumes a new identity, taking a supervisory position in Gretna, Scotland, as Miss Tilly Lockhart.RAF Captain Alex Baird is returning home to Gretna on a secret mission to uncover the saboteur suspected in the Chilwell explosion, as Gretna's factory is likely next. Fearing for his family's safety, he's also haunted by guilt after failing to protect his brother. Alex is surprised to discover a young woman, Miss Lockhart, renting his boyhood room, but the two eventually bond over their mutual affection for his family--until Alex receives orders to surveil her.Rose squirms beneath Alex's scrutiny while she struggles to gain her workers' respect. But when her deception turns to danger, she and Alex must find a way to put their painful pasts behind them and together try to safeguard the future"--